Semillas de concienca | seeds of consciousness: sowing change from the Ecuadorian highlands - Radford, Hope, author; Kwiatkowski, Lynn, advisor; Souza, Caridad, committee member; Van Buren, Mary, committee member (Colorado State University. Libraries, 2024)
This thesis is a small part of Pintag Amaru's story, and mine. I met Pintag Amaru – a small Kichwa organization in Ecuador – in 2022, and this work is the fruit of our collaboration. Focusing broadly on sumak kawsay, a Kichwa principle engaged in Ecuador's 2008 constitution, our research explores Pintag Amaru's understanding, and living out, of the concept. Sumak kawsay has gained recent attention in scholarship as a grassroots "alternative" to the paradigm of international development, but this conversation has rarely included the voices of Indigenous communities at the heart of sumak kawsay's conception and practice. Engaging the central analytical lens of post-development theory and a diversity of anthropological qualitative research methods including participant observation, semi-structured interviews, and focus groups, I explore sumak kawsay through perspectives of – and relationship with – the people of Pintag Amaru. Built collaboratively from the onset, our work seeks to convey Pintag Amaru's grounded understandings on sumak kawsay, development, and their relation as they navigate today's world. Though they see the state's use of sumak kawsay as a co-option of a profoundly expansive and dynamic principle, I find Pintag Amaru conveys creativity and depth of autonomous efforts towards Indigenous resurgence, and sumak kawsay as part of it. They face challenges within the structures of a dominant development paradigm, but navigate these structures strategically to live sumak kawsay out amidst them. Through this work, too, I've come to understand sumak kawsay is dynamic, and deeply tied to place; it is not a prescription for us to replicate. I do believe, however, it is a view of the possible. We hope that this thesis, if nothing else, can offer such an opening – one seed of many – rooting in the cracks of decaying structures to grow something new.
Seeds of consciousness: sowing change from the Ecuadorian highlands
Includes Spanish text.
Keywords: development; environment; sumak kawsay; Ecuador; buen vivir; Indigenous